2003
DOI: 10.1002/eji.200323800
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the course of antigen‐specific CD8 and CD4 T cell responses to a growing tumor

Abstract: Spontaneous tumors frequently express antigens that can be recognized by the immune system but nevertheless manage to evade immune surveillance. To better understand the mechanism of evasion, we followed CD8 and CD4 T cells reacting against a subcutaneously growing tumor, modified to express influenza hemagglutinin (HA) as surrogate tumor antigen. Adoptive transfer of 8,000 antigen-specific CD8 T cells was sufficient to protect against challenge with 1x10 6 tumor cells, while larger numbers of T cells rejected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 30 publications
2
47
1
1
Order By: Relevance
“…These findings have led us to develop tumor-derived antigen-specific vaccine strategies including further exploration of tumor-associated antigens (2) and dendritic cell vaccines for patients with cancer (3, 4). Currently, a potential role of CD4 þ T cells for cancer immunotherapy is being increasingly appreciated (5)(6)(7)(8)(9). Accumulating evidences have shown that tumor-specific CD4 þ T cells eradicate tumors via orchestrating host-derived immune components, especially CD8 þ T cells (7,(10)(11)(12) and natural killer cells (13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings have led us to develop tumor-derived antigen-specific vaccine strategies including further exploration of tumor-associated antigens (2) and dendritic cell vaccines for patients with cancer (3, 4). Currently, a potential role of CD4 þ T cells for cancer immunotherapy is being increasingly appreciated (5)(6)(7)(8)(9). Accumulating evidences have shown that tumor-specific CD4 þ T cells eradicate tumors via orchestrating host-derived immune components, especially CD8 þ T cells (7,(10)(11)(12) and natural killer cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a potential role of CD4 þ T cells for cancer immunotherapy is being increasingly appreciated (5)(6)(7)(8)(9). Accumulating evidences have shown that tumor-specific CD4 þ T cells eradicate tumors via orchestrating host-derived immune components, especially CD8 þ T cells (7,(10)(11)(12) and natural killer cells (13). On the basis of these studies, the efficient induction of tumor-specific, multifunctional effector CD4 þ T cells that provoke antitumor function of other immune cells through their CD40 ligand, interleukin (IL)-2, and IFN-g (5,6,11,14) is now recognized as an important aim of antitumor vaccination strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the recognized importance of Ag-specific CD4 1 T cells in both adaptive and innate immune responses, their identification remains elusive, and their in vitro amplification is hindered by the absence of reliable protocols able to support cell proliferation in the absence of terminal differentiation. While, Ag tumours elicit natural tumour-specific CD4 1 T-cell responses [4][5][6][7][8][9][10], functional tolerance is eventually observed through the induction of T-cell anergy [11,12], T-cell depletion [13] or the limitation of the memory repertoire [10,14,15]. This is possibly due to Ag persistence, and continual TCR signaling, as in the case of chronic viral infections [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Specific CD4 with CD8 cells can reject tumours (Klein et al, 2003). Numerous research studies have focused on probiotics anticancer property exerting resistance to neoplasia and infections (Kato, 2000).…”
Section: Discussionmentioning
confidence: 99%